INCREASE IN THE INTENSITY OF CLINICAL SYMPTOMS AND VENTILATORY DISORDERS IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE DEPENDING ON THE SEVERITY OF THE DISEASE (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
Today, chronic obstructive pulmonary disease is one of the leading causes of morbidity and mortality worldwide, which is constantly growing and represents an important medical and socio-economic problem. At the same time, the relationship between the patient's subjective feelings and objective indicators characterizing the severity of COPD has not been sufficiently studied.